Agroforestry and salt-tolerant trees rehabilitate saline soils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In India a mixture of trees and grass is proving to be an effective way to make saline soils productive. If the right species are grown useful quantities of firewood and forage can be produced. There are more than 900 million hectares of land around...